LAPD '53 - Ellroy, James, 1948-; Martin, Glynn (Abrams Image, 2015)
James Ellroy, the undisputed master of crime writing, has teamed up with the Los Angeles Police Museum to present a stunning text on 1953 LA. While combing the museum's photo archives, Ellroy discovered that the year featured a wide array of stark and unusual imagery-and he has written 25,000 words that illuminate the crimes and law enforcement of the era. Ellroy o ffers context and layers on wild and rich atmosphere-this is the cauldron that was police work in the city of the tarnished angels more than six decades ago. More than 80 duotone photos are spread throughout the book in the manner of hard-edged police evidence.